Implementation of the Everyone Is a Teacher Here (ETH) Learning Model Based on the Mathematical Communication Ability - Valentino Ananda Putra; Marhan Taufik; Reni Dwi Susanti (Mathematics Education Journal, 2023)
Covid-19 has become an epidemic that has most affected the education sector, one of which is the implementation of online learning. Online learning, of course, affects students' mathematical communication. This study aims to apply the ETH (everyone is a teacher here) learning model to overcome problems, especially in students' mathematical communication problems. Based on these objectives, researchers used a qualitative approach. The data was obtained through observation, written tests, and questionnaires and then analyzed to conclude. The results showed that: The application of the ETH-type learning model to the material of a system of linear equations with two variables for three meetings as a whole can be carried out following the steps that have been planned with the acquisition of values that fall into the very good category with the average value of teacher activity in learning the value of 91. Based on the results of student observations conducted by researchers when learning took place, which was divided into four activity activities with an average score of overall activity getting a score of 87.5 with a very good category. In the last activity, Communicating, the average score was 91.7, where students could conclude the material given. These results show positive results where student activity goes very well when using the ETH learning model. The increase in mathematical communication can be seen in the ability of oral mathematical communication to get an average score of 78.3 in the good category. Meanwhile, the increase in written mathematical communication ability can be seen from the post-test results, which are higher than the results of the pretest. Very good, with an average of 87.5. The analysis of student responses gave a positive response to the implementation of ETH-type learning with an average score of 91.9%, and students gave a negative response of 8.1%. Based on these results, it can be concluded that learning through the application of the ETH learning model has achieved indicators of effectiveness.